Pelemahan Institusi Lokal dalam Program Strategis Nasional (PSN) Food Estate di Humbang Hasundutan, Sumatera Utara - Putra, Daniel Pareaktua (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2026)
This paper analyzes the weakening of local institutions in the implementation of the National Strategic Project (PSN) food estate in Humbang Hasundutan Regency, North Sumatra. This program tends to ignore the social context of local communities and local governments. Using a qualitative approach based on literature studies and in-depth interviews, this study finds that the role of the regency government and local communities is increasingly marginalized in decision-making and land management. Using Hindriks' institutional weakness theory framework and motivation-information aspects, this study shows that unequal access to information and the lack of political motivation contribute significantly to the declining influence of local actors. As a result, the program not only failed to achieve significant production outcomes, but also created changes in farmers' social functions and the potential loss of local commodities. This study aims to emphasize the importance of involving local institutions in development programs. As a reflection, this paper recommends that the central government adopt a participatory approach that recognizes the capacity and values of local institutions to achieve more equitable and sustainable food development.